2015
DOI: 10.4238/2015.september.9.8
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphism within the interleukin-28 receptor alpha gene, but not in interleukin-28B, with lower urinary tract symptoms (LUTS) in Chinese

Abstract: ABSTRACT. The aim of this study was to determine the relationship between polymorphisms in the IL-28B and IL-28R genes and lower urinary tract symptoms (LUTS) in Chinese patients. Genomic DNA was extracted from 553 whole blood samples from 233 patients with LUTS resulted from benign prostatic hyperplasia and 320 control subjects. The IL-28B rs12979860 and rs8099917, and IL-28Rα rs10903035 and rs11249006 polymorphisms were genotyped using a polymerase chain reaction-restriction fragment length polymorphism assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…However, chronic periodontitis is still poor understood and the relationship between rs12979860 and rs8099917 and CP has not been reported till now but our results showed that these SNPs were associated with susceptibility to CP. Our finding revealed that most frequently genotypes in CP patients were CT + TT for rs12979860 and GT + GG for rs8099917 which differs from the study of Barreiro et al [43] and Rizk et al [49] but in agreement with many studies by Xiao et al [21], Derbala et al [45], Egli et al [47], Eurich et al [48]. …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…However, chronic periodontitis is still poor understood and the relationship between rs12979860 and rs8099917 and CP has not been reported till now but our results showed that these SNPs were associated with susceptibility to CP. Our finding revealed that most frequently genotypes in CP patients were CT + TT for rs12979860 and GT + GG for rs8099917 which differs from the study of Barreiro et al [43] and Rizk et al [49] but in agreement with many studies by Xiao et al [21], Derbala et al [45], Egli et al [47], Eurich et al [48]. …”
Section: Discussionsupporting
confidence: 81%
“…Recently, Xiao et al [21], Rauch et al [44], Derbala et al [45], Lampertico et al [46], Egli et al [47], Eurich et al [48] have reported that IL-28B polymorphisms associate with the susceptibility to the hepatitis B or C viruses infections, influenza and lower urinary tract symptoms (LUTS). Xiao et al [21] determined the relationship between IL-28B rs12979860 and rs8099917 SNPs and LUTS in Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, only one study has linked SNPs in genes involved in the IFN-λ signaling pathway with an increased risk of bacterial infections. Xiao et al showed that SNP rs10903035 with G allele in the IL28RA was associated with significantly less frequent urinary tract infection (178).…”
Section: Bacterial Infectionsmentioning
confidence: 99%